2009
DOI: 10.2466/pr0.104.3.807-819
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Chinese Superstitious Belief Scale

Abstract: Traditional Western superstitious beliefs, such as black cats and the number 13 bringing bad luck, may not be applicable to different cultures. This study develops a Chinese Superstitious Belief Scale by conducting two studies with 363 and 395 participants, respectively. Exploratory factor analysis was used to construct the scale and then structural equation modeling was applied to verify its reliability and validity. The scale contains six dimensions, Homonym, Traditional customs, Power of crystal, Horoscope,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 29 publications
0
41
0
1
Order By: Relevance
“…These rituals, beliefs and superstitions have been developed from ancient traditions and can still be seen in modern everyday life. For example, a survey by the China Association of Science and Technology showed that the majority of Chinese still hold to the old ways, and as many as 85% of Chinese young people still have their fortunes told (Huang & Teng, 2009;Putzi, 2009).…”
Section: Gamblers' Superstitious Beliefsmentioning
confidence: 98%
“…These rituals, beliefs and superstitions have been developed from ancient traditions and can still be seen in modern everyday life. For example, a survey by the China Association of Science and Technology showed that the majority of Chinese still hold to the old ways, and as many as 85% of Chinese young people still have their fortunes told (Huang & Teng, 2009;Putzi, 2009).…”
Section: Gamblers' Superstitious Beliefsmentioning
confidence: 98%
“…Published questionnaire assessments of luck in previous Chinese studies were unsuitable for use in the study because they did not capture the broad conceptions of luck in diverse gambling and geographical settings (Zheng et al 2010;Huang and Teng 2009;Hernandez et al 2008;Tao et al 2011). For our purposes, items from previous instruments (the Chinese Superstitious Belief Scale, the Superstitious Beliefs Scale, and the Indigenous Inventory Scale) were selected if they assessed prominent content domains of luck found in the literature (Fong 2000;Huang and Teng 2009;Hernandez et al 2008)-i.e., beliefs in the use of homonyms in speech, superstitions behaviours, crystals, Chinese geomancy, horoscopes, and charms to promote luck.…”
Section: Chinese Beliefs In Luck Scale (Cbls)mentioning
confidence: 99%
“…For our purposes, items from previous instruments (the Chinese Superstitious Belief Scale, the Superstitious Beliefs Scale, and the Indigenous Inventory Scale) were selected if they assessed prominent content domains of luck found in the literature (Fong 2000;Huang and Teng 2009;Hernandez et al 2008)-i.e., beliefs in the use of homonyms in speech, superstitions behaviours, crystals, Chinese geomancy, horoscopes, and charms to promote luck. A panel of seven Chinese people from a variety of East and Southeast countries (Singapore, China, Hong Kong, Malaysia) then indicated whether the collated items from previous scales were relevant to Chinese people from their own country of origin.…”
Section: Chinese Beliefs In Luck Scale (Cbls)mentioning
confidence: 99%
See 1 more Smart Citation
“…Important to many people, horoscopes are inherent to superstition ideologies (Fichten and Sunerton, 1983;Huang and Teng, 2009). As such, superstitious beliefs help explain the routine nature of reading horoscopes (Kramer and Block, 2008).…”
Section: H4mentioning
confidence: 99%